Peran Ekuitas Swasta dalam Penyelesaian Bank Gagal Pascakrisis Keuangan dan Implikasinya terhadap Stabilitas Keuangan - Grace Yulianti; Benardi Benardi; Seger Santoso (Jurnal Visi Manajemen, 2024)
This study aims to analyze the role of private equity in resolving failed banks following the 2008 financial crisis and its impact on financial stability. Using a qualitative literature review method, this research examines 30 related studies covering restructuring efficiency, capital stability, operational innovation, and market concentration risks. The findings indicate that private equity can expedite the resolution of failed banks through effective restructuring and improved operational efficiency. However, challenges such as moral hazard risks and market concentration require strict regulatory oversight. The contribution of private equity to financial stability is contextual, depending on market structures and local regulations. This research provides strategic insights for policymakers to optimize the benefits of private equity in the financial sector.